The Plasticity of Circulating Tumor Cells in Ovarian Cancer During Platinum-containing Chemotherapy - Gening, Snezhanna O.; Dolgova, Dinara Rishatovna; Abakumova, Tatyana Vladimirovna; Antoneeva, Inna Ivanovna; Gening, Tatyana Petrovna (Current Cancer Drug Targets, 2021)
Background: Circulating Tumor Cells (CTCs) are a potential source of metastases and relapses. The data on molecular characteristics of Ovarian Cancer (OC) CTCs are limited. Objective: This study aims to assess the TGFβ, CXCL2, VEGFA and ERCC1 expressions in two OC CTC subpopulations before and during chemotherapy (CT), and their relation to clinical characteristics. Methods: Two CTCs subpopulations (EpCAM+CK18+E-cadherin+; EpCAM+CK18+Vimentin+) were enriched using immunomagnetic separation before treatment and after 3 cycles of platinumcontaining CT. The expression of mRNA was assessed using RT-qPCR. Results: The study included 31 I-IV stage OC patients. During CT, TGFβ levels increased in both fractions (p=0.054) compared with the initial levels. ERCC1 expression in E-cadherin+ CTCs was higher during neoadjuvant than adjuvant CT (p=0.004). CXCL2 level in E-cadherin+ CTCs increased (p=0.038) during neoadjuvant CT compared with the initial. TGF-β expression in vimentin+ CTCs during CT was negatively correlated to disease stage (p=0.003). Principal component analysis before CT revealed a component combining VEGFA, TGFβ, CXCL2, and a component with ERCC1 and VEGFA; during CT, component 1 contained ERCC1 and VEGFA, and component 2 - TGFβ and CXCL2 in both fractions. Increased ERCC1 expression in E-cadherin+ CTCs during CT was associated with decreased Progression-Free Survival (PFS) (HR 1.11 (95% CI 1.03-1.21, p=0.009) in multivariate analysis. Conclusion: EpCAM+ OC CTCs are phenotypically heterogeneous, which may reflect variability in their metastatic potential. CT changes the molecular characteristics of CTCs. Expression of TGFβ in EpCAM+ CTCs increases during CT. High ERCC1 expression in EpCAM+CK18+E-cadherin+ CTCs during CT is associated with decreased PFS in OC.
Keywords: CXCL2